Regional Policy Coherence for the Great Green Wall Initiative: Soil Health as the Foundation to Realising the Ambitions of the Great Green Wall Initiative - African, Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Healthy soil is the foundation of resilient landscapes, sustainable food systems, and climate adaptation in Africa’s drylands. As a unifying element across climate, nutrition, biodiversity, and restoration agendas, soil health plays a critical role in realising the ambitions of the African Union’s Great Green Wall Initiative (GGWI). With over 65% of productive land degraded and soil erosion undermining agricultural productivity, smallholder farmers across the continent face compounding vulnerabilities. The GGWI Strategy (2024–2034) recognises soil health as central to reversing land degradation and building long-term resilience, aligning closely with the Africa Fertiliser and Soil Health Action Plan (AFSH-AP) (2023 – 2033) and broader goals outlined in the Ten-Year Comprehensive Africa Agriculture Development Programme (CAADP) Strategy and Action Plan (2026-2035).